From Sharing to Business: Urban and Social Dynamics of Airbnb in Naples - Napoletano, Feliciano (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
This research focuses on the spatial distribution of Airbnb listings in Naples, examining how this phenomenon influences the urban and socioeconomic dynamics of the city. Through a detailed analysis of data collected from 2015 to 2023, the study highlights the significant impact of Airbnb on the processes of gentrification and touristification, showing how the platform has contributed to transformations in the real estate market and the social composition of neighborhoods. Using GIS techniques to map the concentration of listings, the research reveals a growing professionalization of hosts and an intensification of property use as short-term rentals, increasingly shifting the platform’s use from a shared to a commercial economy. The work also proposes a reflection on the urban policies needed to mitigate the negative effects of these dynamics and promote sustainable urban tourism.